Supercapacitor Devices Based on Graphene Materials - Wang, Y.; Shi, Z.; Huang, Y.; Ma, Y.; Wang, C.; Chen, M.; Chen, Y.
Graphene materials (GMs)as supercapacitor electrode materials have been investigated. GMs are prepared from graphene oxide sheets, and subsequently suffer a gas-based hydrazine reduction to restore the conducting carbon network. A maximum specific capacitance of 205 F/g with a measured power density of 10 kW/kg at energy density of 28.5 Wh/kg in an aqueous electrolyte solution has been obtained. Meanwhile, the supercapacitor devices exhibit excellent long cycle life along with ¡90